Metastatic endometrial carcinoma presenting as a scapular mass: A case report and literature review - Eccita Rahestyningtyas; Wita Saraswati (Elsevier, 2024)
Bone metastases of endometrial cancers are quite rare, especially in the scapula. Only two previous reports of such cases were found in the literature, and in each case a different approach to diagnosis was used. There are no established recommendations for screening for bone metastases at diagnosis or after initial treatment of endometrial cancers. In the present case, a 55-year-old woman with progressive abdominal distension was diagnosed with a cystic mass. Histopathological analysis revealed grade II synchronous endometrioid carcinoma in both the endometrium and the ovaries. The patient received three cycles of combined paclitaxel and carboplatin chemotherapy. Seven months after the last chemotherapy cycle, a palpable lump was found in the right shoulder, suggesting a lesion in the right scapula. A bone scan revealed heightened radioactivity uptake, highlighting the unpredictable nature of the disease progression. The choice of diagnostic imaging modality remains challenging. This case emphasises the need for ongoing investigation of the mechanisms of distant metastasis and for the development of standardised diagnostic and therapeutic strategies.